Visual merchandising: comparison of shelf hiring of different Fmcg companies and its impact on sales - Niloy, Sadman Sawmik (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.